New Macroseismic and Morphotectonic Constraints to Infer a Fault Model for the 9 (Mw6.1) and 11 January (Mw7.3) 1693 Earthquakes (Southeastern Sicily) - Pirrotta, C.; Barbano, M. S. (Frontiers in Earth Science, 2020)
This study deals with the earthquakes occurred in southeastern Sicily in 1693 (9 and 11 January, Mw≈6.1 and 7.3, respectively). Although they have been largely studied, robust and commonly accepted seismic sources are still missing. We performed a revision of the 1693 macroseismic data and, for the fore and main-shocks, modelled new NNE-SSW trending seismic sources. In the Hyblean Plateau area, we carried out an analysis of DEM and aerial photos to map tectonic feactures. Then, we performed field surveys on the main faults, and a morphotectonic study with the aim of characterizing the activity of mapped faults. The study revealed the presence of three main fault systems. The first is the Palazzolo-Villasmundo Fault System, composed of NNE-SSW and NE-SW trending north-west-dipping normal faults. Some of these faults could be reactivated as reverse faults. The second is the Augusta-Floridia Fault System, made of NNW-SSE and NW-SE normal faults. The third is composed of faults never mapped before: the Canicattini-Villasmundo Fault System that shows both segmented and stepping, almost N-S trending and west-dipping normal faults; some of these faults show a left-lateral movement. The morphotectonic study demonstrated that the fault systems are active. Furthermore, both strike and kinematics of the studied faults well match with the regional stress field characterized by a NW-SE σ1, which in the study area is probably both affecting some pre-existing faults, the Palazzolo-Villasmundo and the Augusta-Floridia Fault Systems, and causing the formation of new faults, the Canicattini-Villasmundo Fault System. The latter system lies across the Hyblean Plateau with a total length of 35 km and, due to its aligned segmented pattern, it can be the surface expression of a master fault that seems dividing the Hyblean Plateau in two blocks. Moreover, the Canicattini-Villasmundo Fault System well fits the southern part of the 1693 revaluated seismic sources and matches with a current alignment of shocks mainly characterized by left-lateral focal mechanisms on almost N-S fault planes. Considering the possible rupture length in depth, it could manage to release Mw ≈ 7.1 earthquakes, representing a valuable candidate source for the 1693 earthquakes.